Effect of PGPR and BCA on Quality Seed Production of Bell Pepper (Capsicum annuum L.) under Open Field Conditions - Kumari, Sujata; Bharat, Narender K.; Thakur, Ashok K.; Kaushal, Rajesh (International Journal of Economic Plants, 2020)
A field experiment was conducted during two consecutive seasons of 2016 and 2017 at experimental farm of Department of Seed Science and Technology, Dr YS Parmar University of Horticulture and Forestry, Nauni, Solan-173230 (HP). The effect of Plant growth promoting rhizobacteria (PGPR) and biocontrol agent (BCA) was evaluated by applying as seedling root dip and soil application alone and in various combinations. The study revealed that plant growth, crop yield and seed yield parameters like maximum plant height (75.43 cm), minimum days to 50% flowering (54.34 days), maximum number of fruitsplant-1 (7.75), maximum average fruit weight (48.46 g), fruit length (6.78 cm), fruit width (6.48 cm), fruit size (44.37 cm2), minimum days to first picking (102.43), maximum harvest duration (41.97 days), maximum number of fruit pickings (9.10), highest fruit yield plant-1 (1038.54 g), fruit yield plot-1 (15.58 kg) and fruit yield ha-1 (450.37 q), maximum number of seeds fruit-1 (177.51), seed yield plant-1 (15.78 g), seed yield plot-1 (236.63 g), seed yield ha-1 (673.50 kg) were recorded maximum with treatment T5 PGPR (seedling root dip)+Trichoderma harzianum (soil application).The effect of all the treatments was significantly higher during the trial conducted in 2016 as compared to the trial conducted in 2017.